Thinking Narratively : Between Novel-Essay and Narrative Essay. - Fusillo, Massimo; Simonetti, Gianluigi; Marchese, Lorenzo (Berlin/Boston : Walter de Gruyter GmbH, 2022)
The series explores the complexity and the interconnections of arts and languages by merging, comparing and contrasting themes from different sources, methodologies or fields of studies. Its main results derive from the "Arts, Languages, and Media: Translation and Transcodification" project but it is also open to monographs and edited volumes arisen from different contexts and projects.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books